Fatima Espin Labra: capstone - Espin Labra, Fatima, artist (Colorado State University. Libraries, 2024)
The artist's statement: My name is Fatima Espin, and I am a senior student at CSU, majoring in graphic design with a business minor. I believe that designers have a significant role in society, and that is not only to create aesthetically beautiful and informative work but to also bring awareness to critical issues that capture people's attention. Moreover, I hope that I can inspire young generations of artists and Latinx individuals to pursue their dreams of making art as a living. My art style is characterized by its bright and vibrant colors, which I use to express my creativity. I enjoy researching new topics that interest me and integrating them into my work, I like to push boundaries on what design could mean and try to create impactful design that resonates with viewers even after they've seen it. I am inspired by my community of first-generation students and my Mexican heritage to create work that can make a change and give art a new perspective so that it can be acknowledged as a powerful tool and a successful career. I believe that aesthetics are essential in design, but I believe that as designers, we have a broader task, which is to develop material that can make a difference.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design